Linguocultural analysis of the concepts of “Bildung” and “Erziehung” in the German language (Texas Journal of Multidisciplinary Studies, 2025)
This article analyzes the history, semantic development and linguocultural characteristics of the concepts of “Bildung” and “Erziehung” in the German language. The study shows the formation and transformation of the concept of “Bildung” as a cultural and educational phenomenon in German society, reveals its meanings and social context in different historical periods. Also, based on encyclopedic and etymological sources, the spiritual, moral and intellectual content of “Bildung” is widely studied. The article sheds light on issues such as society’s attitude to education, social status, and personal development through the development of the concept. The results of the study demonstrate the close connection of the concept of “Bildung” with national identity and cultural values.